Penggunaan Karbon Daun Aren dan Bleaching Earth dalam Penjernihan Bertahap Minyak Jelantah - Aura Dwi Qalbi; Umar Kalmar Nizar (MASALIQ, 2026)
Repeated use of cooking oil causes a decline in oil quality due to the formation of free fatty acids, polar compounds, and oxidation products. This study aimed to evaluate the effect of variations in the composition of sugar palm leaf carbon (Arenga pinnata) and bleaching earth on the quality of used cooking oil through an adsorption-based purification process. Sugar palm leaf carbon was obtained through carbonization at 300 °C for 1 hour and was then characterized using proximate analysis. The purification process was conducted using three adsorbent compositions, namely K75-B25, K50-B50, and K25-B75. Adsorption effectiveness was evaluated based on density, flow rate, acid value, and saponification value. The proximate analysis results showed that sugar palm leaf carbon had a moisture content of 4.49%, a volatile matter content of 2.20%, an ash content of 9.00%, and a fixed carbon content of 88.8%. All treatment variations improved the quality of used cooking oil compared with the untreated sample. The K75-B25 treatment demonstrated the best performance, with the lowest density of 0.9407 g/mL, the highest flow rate of 0.3227 mL/s, the lowest acid value of 4.8378 mg KOH/g, and the highest saponification value of 50.9149 mg KOH/g. These findings indicate that increasing the proportion of sugar palm leaf carbon resulted in greater adsorption effectiveness than increasing the proportion of bleaching earth. Thus, sugar palm leaf carbon combined with bleaching earth has the potential to be used as an alternative adsorbent to improve the physicochemical characteristics of used cooking oil through a purification process.